Illness representations in chronic diseases: A literature review - Rahayu, Sri; Rahayuningsih, Faizah Betty; Indriyani, Yeni; Azkiya, Arifatul; Baety, Nimas Citra Nur; Pratiwi, Jiheny Siska (Universitas Aisyah Pringsewu, 2023)
The prevalence of chronic illnesses, including hypertension, stroke, heart failure, diabetes mellitus, cancer, and chronic kidney disease, is rising globally. The primary causes of death and disability among patients are these kinds of illnesses. Consequently, healthcare professionals must focus more on these illnesses. This study aims to collect and examine articles related to illness representations in chronic diseases. A search for relevant literature was conducted using the following keywords: